Twenty-year temporal and regional trends in heart transplantation in Europe: results from the Global Observatory on Donation and Transplantation (GODT). (14th October 2021) - Manla, Y; Al Badarin, F.J; Soliman, M; Gobolos, L; Alsindi, F; Bader, F
Abstract: Introduction: Heart transplant (HT) remains the only cure for patients with advanced heart failure. However, limited supply of donors continues to be the main obstacle to growing transplant programs around the world. Since population changes are not uniform, describing temporal trends in availability of donors and in number of transplanted hearts will provide better understanding of regional variations in organ availability and allocation. Purpose: We aim to evaluate temporal and regional trends in number of brain-dead donors (BDDs) and its association with the number of heart transplants (HTs) in Europe between 2000 and 2019. Methods: Global Observatory on Donation and Transplantation (GODT) represents the world's most comprehensive source of data on organ donation and transplantation. Available data were collected for all European countries for the years (2000–2019) except for the year 2005. Geographical classification (north, west, central, south) was made according to EuroVoc definition. Trends of HTs and BDDs were assessed using Joinpoint Software of the National Cancer Institute to calculate the annual percentage change (APC) and reported as per million population (PMP). The linear correlation coefficient was assessed using R studio. Results: Over the past two decades, there was a 35% increase in HTs PMP rate in Europe from the year 2000 to 2019 with an APC of 1.4% (95% CI [1.1–1.7], P<.0001). This change was more pronounced in Central Europe, where HTs PMP rate increased from 0.65 in 2000 to 2.93 in 2019 (APC 9.9% (95% CI [8.1–11.8], P<.0001)) and in Northern Europe, where HTs PMP rate increased from 2.97 in 2000 to 5.18 in 2019 (APC 2.7% (95% CI [1.8–3.7], P<.0001)) (Figure 1). Despite the increase in BDDs in Europe between 2000–2019 (from 3.62 to 12.25 donors PMP) (Figure 2), the association between increased BDDs and HTs varied between regions, with a very strong association in Central Europe (r=0.95, P<0.0001) and strong correlation in Northern Europe (r=0.64, P=0.003). However, positive correlation between BDDs and HTs was not seen in Southern or Western Europe (r=−0.52, p-value=0.02, r=0.02, p-value=0.94, respectively). Conclusion: The number of BDDs has increased in Europe in the past two decades with a concomitant increase in HT volumes. A regional variation in the relationship between the number of BDDs and HTs was observed among European subregions, such that it was most pronounced in Central Europe. Understanding the reasons underlying these disparities can potentially inform improvement in organ allocation systems throughout Europe. Funding Acknowledgement: Type of funding sources: None.